Supramolecular Chemistry 2012
DOI: 10.1002/9780470661345.smc147
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorbed Self‐Assembled Monolayers

Abstract: A review of the fundamental aspects of chemisorbed self‐assembled monolayers (SAMs), as a tool for building complex molecular systems on solid surfaces, is presented. Using alkanethiols, SAMs, as model systems the self‐assembly, surface structures, and SAM stability under different experimental conditions are discussed. We also point out the characteristics of SAMs that make them suitable especially for building active micro‐ and nanostructured molecular systems on surfaces, and stress their limitations result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 109 publications
1
3
0
Order By: Relevance
“…These were demonstrated by the island-shaped morphology of the additional layer after the CuAAC reactions, which were consistently observed within the Au grains and located at some distance away from the grain edges (Figure c,d). These results correlate well with the reported models and studies showing characteristic defects at the Au grain edges, where the SAM molecules are typically disordered, less compact, and of varied orientations. ,,, Moreover, the orientation, conformation, and density of the SAM molecules could influence the surface reactivity of the SAMs. , A recent study on the azide-terminated monolayers on the silica surface reported that the packing density of molecules could affect the interaction of adjacent azide groups, such that the azide groups adopt a more parallel orientation relative to the surface through dipole-dipole interactions in less compact monolayers . In the case of the N 3 -EG 6 -SAMs, the density and orientation of the molecules and azide functionalities, particularly around structural defects, may affect the kinetics of the interfacial reactions, such as CuAAC click functionalization (Figure f).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These were demonstrated by the island-shaped morphology of the additional layer after the CuAAC reactions, which were consistently observed within the Au grains and located at some distance away from the grain edges (Figure c,d). These results correlate well with the reported models and studies showing characteristic defects at the Au grain edges, where the SAM molecules are typically disordered, less compact, and of varied orientations. ,,, Moreover, the orientation, conformation, and density of the SAM molecules could influence the surface reactivity of the SAMs. , A recent study on the azide-terminated monolayers on the silica surface reported that the packing density of molecules could affect the interaction of adjacent azide groups, such that the azide groups adopt a more parallel orientation relative to the surface through dipole-dipole interactions in less compact monolayers . In the case of the N 3 -EG 6 -SAMs, the density and orientation of the molecules and azide functionalities, particularly around structural defects, may affect the kinetics of the interfacial reactions, such as CuAAC click functionalization (Figure f).…”
Section: Resultssupporting
confidence: 86%
“…These results correlate well with the reported models and studies showing characteristic defects at the Au grain edges, where the SAM molecules are typically disordered, less compact, and of varied orientations. 37,44,54,55 Moreover, the orientation, conformation, and density of the SAM molecules could influence the surface reactivity of the SAMs. 44,56 A recent study on the azide-terminated monolayers on the silica surface reported that the packing density of molecules could affect the interaction of adjacent azide groups, such that the azide groups adopt a more parallel orientation relative to the surface through dipole-dipole interactions in less compact monolayers.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The AT electrodes do not contain any crystalline characteristics (Figure a), suggesting that the surface of the AT electrodes does not allow for the formation of highly ordered, high-quality monolayers, but instead that the monolayers may contain defects that allow for nonspecific adsorption of the MB-tagged DNA to the electrode. The nonspecific adsorption of biomolecules (namely, single-stranded DNA) to an imperfect self-assembled monolayer is well-established. This interaction would inhibit biosensor performance by decreasing solvent access to the biorecognition elements. , This may also explain why the MB signal ratio for some of the AT electrodes upon treatment is greater than one (Figure b).…”
Section: Discussionmentioning
confidence: 99%
“…Supramolecular (i.e., noncovalent) interactions play an essential role in a wide variety of functions, ranging from the formation of colloids, metabolic processes, and medical therapies to biosensing applications such as wearable and flexible monitoring. The in situ monitoring of the components participating in supramolecular interactions is of great importance to better understand and, thus, design, develop, or optimize the applications that involve them. , In particular, the association between polyamines and phosphates is an important type of supramolecular bond that has significant implications in various biological systems. Although electrostatic interactions are the primary driving force for the creation of polyamine–phosphate assemblies, hydrogen bonds are also believed to play a crucial role in stabilizing their structure. , One example is the formation of nuclear aggregates of biogenic polyamines, such as putrescine, spermidine, and spermine, and orthophosphate anions (Pi) in many replicating cells . These aggregates hierarchically assemble into cyclic structures with high order that can protect DNA .…”
Section: Introductionmentioning
confidence: 99%